Monitoring equity in the delivery of health services: a Delphi process to select healthcare equity indicators (Swiss Medical Weekly, 2024)
AIMS OF THE STUDY: Health equity is a key component of quality of care and an objective for a growing number of quality improvement projects for deontological, ethical, public health and economic reasons. To monitor equity in the delivery of health services in Switzerland, there is a need to implement valid, measurable and actionable equity indicators, along with vulnerability stratifiers such as migrant status, which could lead to differences in quality of care. The aim of this study was to develop a set of healthcare equity indicators and stratifiers targeting inpatient and outpatient populations and to test their feasibility.METHODS: A scoping literature review and inputs from a national interprofessional expert taskforce provided a set of indicators and vulnerability stratifiers. The most valid and measurable indicators and stratifiers were retained using a Delphi process. They were then operationalised, and their implementation tested in three Swiss hospitals from the three language regions.RESULTS: A taskforce of 18 experts, including a patient representative, selected 11 indicators that evaluate structures, processes and outcomes, and five vulnerability stratifiers. Although most indicators and stratifiers could be implemented in all three hospitals, data availability was limited for some variables, including patient satisfaction and access to interpreters for foreign-language patients.CONCLUSIONS: The equity indicators and stratifiers identified by this two-stage process have content validity, wide patient coverage and are focused on inequities in the healthcare system that are actionable through improvement projects. Both the indicators and the project methodology could be replicated in institutions aiming for more equitable care.